2019
DOI: 10.1177/2164956119879872
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Psychological Distress Profiles and their Correlates in Interdisciplinary Health-care Professional Students

Abstract: BackgroundHealth-care professional (HCP) students experience high levels of burnout, characterized by work- and school-related stress. Burnout is associated with a host of negative psychological and health outcomes. It may also contribute to cognitive dysfunction and decreased work productivity and may be related to trait mindfulness. This study cross-sectionally explored psychological distress and its correlates in a sample of interdisciplinary HCP students using cluster analysis.MethodFifty-seven interdiscip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Health care students typically have a high academic workload, pressure from high-stakes assessments, and exposure to diverse patient issues when out on placements. Unfortunately, students may experience mental health issues and mental distress including sleeping problems, depression, anxiety, stress, and suicide risk [ 1 , 2 , 3 ]. This can also lead to impaired cognitive functioning and burnout, which negatively impacts students’ academic performance and student experience [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health care students typically have a high academic workload, pressure from high-stakes assessments, and exposure to diverse patient issues when out on placements. Unfortunately, students may experience mental health issues and mental distress including sleeping problems, depression, anxiety, stress, and suicide risk [ 1 , 2 , 3 ]. This can also lead to impaired cognitive functioning and burnout, which negatively impacts students’ academic performance and student experience [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple sources of stress for health professions students including academic (e.g., grades and classroom performance), clinical (e.g., productivity demands, complex cases) and personal (e.g., work-life balance, financial). Stress and burnout negatively impact students’ personal and professional lives and are associated with academic challenges, 3 unprofessional behavior, 4 poor quality clinical care, 5 and greater physical and emotional symptoms. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Stress and burnout negatively impact students’ personal and professional lives and are associated with academic challenges, 3 unprofessional behavior, 4 poor quality clinical care, 5 and greater physical and emotional symptoms. 3 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Studies have shown that professionals and students in the field of healthcare have burnout levels that can be considered high in relation to those of other professions. [8][9][10][11] A previous study by our research group found that 58.1% of physicians who work in oncology had two-dimensional burnout. 10 In another study, we found that 44.9% of medical students also had levels compatible with two-dimensional burnout.…”
Section: Introductionmentioning
confidence: 93%